The rhetoric of Senator Loren Legarda her place in the advocacy of addressing the climate change issues in the Philippines - Caballes, Lidelyn Jane M.
This study was conducted in view of the significance of rhetoric not only in figuring out the motives of Senator Loren Legarda in delivering her environmental speeches in the Plenary Hall of the Senate, but also in recognizing her place in the advocacy of addressing the climate change issues in the Philippines. The study aimed to analyze and determine the kind of rhetoric Senator Loren Legarda had in her environmental speeches that addressed issues on climate change in the Philippines, which were delivered during formal sessions in the senate. The Dramatistic Pentad of Kenneth Burke with its five elements in the pentad were used in scrutinizing the privilege speeches of Senator Loren Legarda. Also, this tool for analysis was the key mechanism used in drawing a description of the kind of rhetoric Senator Loren Legarda had from the speeches she delivered addressing environmental concerns. Five privilege speeches, which addressed the issue on climate change, of Senator Loren Legarda, were the primary data used in this study. And to have a visual representation of how the five elements in the pentad were employed in theses speeches, the researcher constructed a framework for analysis that positioned the elements with its defined levels. This framework described the roles of each element, and how it affects one another. After the five elements in the pentad were identified in every speech, and after thorough examination on how these elements affect each other, it was found out that the scene has great influence on the agent, whose acts provided rational sequencing of events along with various agencies in order to come up with unequivocal presentation of purposes. It was conclusive that the kind of rhetoric Senator Legarda had in the five privilege speeches addressing the issue on climate change in the Philippines was brought about by the agent's significant role in the advocacy of addressing te climate change in the Philippines. Limited studies in the Philippines setting have been found in this area, thus, results of this study would provide additional information on rhetorical criticism using the Dramatic Pentad of Kenneth Burke.
Thesis, Undergraduate (BA Communication Arts) -- U. P. in Mindanao
Keywords: Communication Arts -- Speech Communication